A Comprehensive Review of School‐Based Body Mass Index Screening Programs and Their Implications for School Health: Do the Controversies Accurately Reflect the Research?1. (January 2015) - Ruggieri, Dominique G.; Bass, Sarah B.
ABSTRACT BACKGROUND Whereas legislation for body mass index (BMI) surveillance and screening programs has passed in 25 states, the programs are often subject to ethical debates about confidentiality and privacy, school‐to‐parent communication, and safety and self‐esteem issues for students. Despite this debate, no comprehensive analysis has been completed that compares and contrasts how these issues differentially affect schools, parents, and students. METHODS A keyword search from electronic databases a review of state legislation related to BMI surveillance screening was used to identify relevant literature data focused on surveillance screening policies, BMI report cards, parental perceptions of BMI screenings their child's weight status. RESULTS This article addresses the gap of previous literature by outlining the ethical considerations and implications that BMI screening programs and report cards have for schools, parents, and students, and links these with outcome studies to address whether these controversies are supported by research. CONCLUSIONS Despite the controversies surrounding these programs, this review shows that they can be valuable for all parties and demonstrates BMI screening programs to be vital to the development of robust school‐based obesity prevention programs and promotion of healthy lifestyles in schools.